Analysis of Amnesty International Success in Enforcing Human Rights in Deep South - reza adam (Mediasi: Journal of International Relation)
This study aims to understand the reasons why Amnesty International succeeded in enforcing human rights in the Deep South of Thailand's conflict. The Deep South conflict of Thailand has its roots in historic problems, since the annexation of the Patani Kingdom by the Siamese kingdom, which is now Thailand's state. Conflict which initially emerged as inter-ethnic conflict of Malay and Thai slowly transitioned into inter-Religion, Islam and Buddhism. The Deep South community as a Muslim identity feels discrimination by the Thai government as a Buddhist identity. On this issue, the Deep South people made a resistance movement to defend them against discrimination. The Thai government regards the movement as a separatist movement that means rebellion. To stem the resistance, the Thai government, then, formulated a series of laws that facilitate its tools to commit human rights abuses such as torture and detention, when the Deep South community as a local people has no access or influence to the Thai authorities. In view of these conditions, Amnesty International as an International Human Rights organization makes a successful effort to enforce human rights in the conflict. Using the Transnational Advocacy Network concept, this study explains the successes of Amnesty International. The approach used is Leverage Politics and Accountability Politics to be able to understand the successes made by Amnesty International. Both approaches are used in analyzing the success of Amnesty International in forming advocacy networks, influencing powerful actors, and pressuring the Thai government through advocacy networks. This research applies Qualitative Method, with data collection through Library Research. In this study it will also be discussed slightly about the Islamic Worldview of human rights. The researcher hoped that both state and non-state actors can understand the success of Amnesty International's role, similar steps in international dynamics, and be a reference for academics to develop this research.